Islamic Legal Reform and the Principle of Moderation: A Study of Indonesian Family Law - Ilma, Mughniatul (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2025)
The ethos of moderation (wasaṭiyyah) serves as a foundational principle in Islamic law, particularly within the domain of family law. However, the codification of Islamic law into state legislation raises a critical question: Does the legal positivization of these norms reinforce, constrain, or obscure the spirit of moderation? This article examines how the principle of moderation is articulated and institutionalized in the reform of Islamic family law in Indonesia, with particular reference to Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law. Utilizing a normative legal methodology with a conceptual and statutory approach, this study finds that the reforms reflect key values of moderation, particularly in provisions concerning the minimum age of marriage, the status of children born out of wedlock, and the regulation of polygamy. These developments demonstrate a conscious effort to balance Sharia with evolving societal needs, uphold justice, and integrate local wisdom and universal human rights. In doing so, Indonesia's model of Islamic family law reform illustrates how Islamic legal principles can remain both contextually responsive and normatively grounded in the ethical vision of Islam.